Biphasic contrast medium injection in cardiac CT: moderate versus high concentration contrast material at identical iodine flux and iodine dose - Rutten, Annemarieke (Springer-Verlag, 2010)
OBJECTIVE: To prospectively investigate the influence of contrast material concentration on enhancement in cardiac CT by using a biphasic single-injection protocol. METHODS: Sixty-four-row multidetector cardiac CT angiography was performed in 159 patients randomised to a moderate or high contrast medium concentration. Contrast material injection included a first phase for enhancement of the coronary arteries and a second phase, at half the iodine flux, targeted at enhancement of the right ventricle. Contrast medium injection was followed by a saline flush. For both concentrations, injection duration (and thus total iodine dose) was adapted to the duration of the CT data acquisition and iodine flux was adjusted to patient weight. Attenuation was measured at various levels in the heart and vessels and the two concentrations compared, overall and per weight group. RESULTS: Enhancement of the aorta and left ventricle was significantly greater with the moderate than with the high concentration contrast medium. This remained true for the two higher weight groups. No difference was found in the lowest weight group or in the right ventricle and pulmonary outflow tract. CONCLUSION: With a biphasic injection protocol, enhancement of the aorta and left ventricle was weaker with the higher concentration of contrast material.